2013
DOI: 10.1002/lary.23893
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Dietary Influences on Nosebleed Severity in Hereditary Hemorrhagic Telangiectasia

Abstract: ObjectiveTo identify factors influencing the severity of epistaxis in hereditary haemorrhagic telangiectasia. Study designParticipants with and without hereditary haemorrhagic telangiectasia were recruited from a specialist UK service, and online following advertisement by the HHT Foundation International. Both groups were asked to complete a non-biased questionnaire. MethodsThe reported effects of specific treatments or lifestyle factors on epistaxis were assigned positive values if beneficial, negative value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 56 publications
4
60
0
4
Order By: Relevance
“…However, in recent studies by our group, HHT patients reported that nosebleeds could be precipitated by certain food groups (13,14). Spontaneously volunteered precipitant foods included red wine, spices, chocolate, coffee, berries, oily fish, and other food items that contain high levels of naturally occurring salicylates and other anti-platelet agents (13). We hypothesised that for some people, suggesting dietary changes may also detrimentally impact on their quality of life, and therefore examined nosebleed relationships with dietary supplements that may be more readily modified.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, in recent studies by our group, HHT patients reported that nosebleeds could be precipitated by certain food groups (13,14). Spontaneously volunteered precipitant foods included red wine, spices, chocolate, coffee, berries, oily fish, and other food items that contain high levels of naturally occurring salicylates and other anti-platelet agents (13). We hypothesised that for some people, suggesting dietary changes may also detrimentally impact on their quality of life, and therefore examined nosebleed relationships with dietary supplements that may be more readily modified.…”
Section: Introductionmentioning
confidence: 81%
“…HHT nosebleeds are highly variable, and generally difficult to predict. However, in recent studies by our group, HHT patients reported that nosebleeds could be precipitated by certain food groups (13,14). Spontaneously volunteered precipitant foods included red wine, spices, chocolate, coffee, berries, oily fish, and other food items that contain high levels of naturally occurring salicylates and other anti-platelet agents (13).…”
Section: Introductionmentioning
confidence: 96%
“…The alteration in the signaling pathways causes abnormal development of blood vessels, such as dilated venules (eg, telangiectasias) and open arteriovenous channels. 9 The current understanding is that some unknown vessel injury causes angiogenic stimulation, which results in the vessels' inability to mature correctly.…”
Section: Background and Pathophysiologymentioning
confidence: 99%
“…In a study of 43 patients with HHT, the results suggested that the antioxidant might decrease the severity and frequency of diurnal epistaxis, but it was most effective in men. 34 Silva et al 9 found that most treatments were temporary measures and that most therapies needed repetition. They also found that avoidance of fish oils and high-sali cylate foods (eg, alcohol, red wine, cayenne pepper, capsicum, chocolate, coffee) was associated with a decrease in epistaxis.…”
Section: Epistaxis Managementmentioning
confidence: 99%
“…It varies in severity and frequency but can significantly affect patients' quality of life (30)(31)(32)(33) . Certain foods, often those containing high salicylate levels, have been reported to worsen epistaxis, as have low humidity and changes in temperature (34) . Various subjective grading systems are available (35,36) , and objective classification of the pattern of lesions has also been described (37) .…”
Section: Clinical Featuresmentioning
confidence: 99%